Rethinking cancer a new understanding for the post-genomics era - Bertolaso, Marta; Bissell, Mina; Ernberg, Ingemar 1948-; Strauss, Bernhard (Vienna series in theoretical biology, 2021)
"Steps toward an explanatory paradigm for cancer that integrates its different levels of organization (molecular, genetic, etc.) and also integrates theoretical and experimental biology with oncology"--